Time-kill and synergism studies of ceftobiprole against Enterococcus faecalis, including β-lactamase-producing and vancomycin-resistant isolates (2007)
Ceftobiprole (BAL9141) is an investigational cephalosporin with broad in vitro activity against gram-positive cocci, including enterococci. Ceftobiprole MICs were determined for 93 isolates of Enterococcus faecalis (including 16 β-lactamase [Bla] producers and 17 vancomycin-resistant isolates) by an agar dilution method following the Clinical and Laboratory Standards Institute recommendations. Ceftobiprole MICs were also determined with a high inoculum concentration (107 CFU/ml) for a subset of five Bla producers belonging to different previously characterized clones by a broth dilution method. Time-kill and synergism studies (with either streptomycin or gentamicin) were performed with two β-lactamase-producing isolates (TX0630 and TX5070) and two vancomycin-resistant isolates (TX2484 [VanB] and TX2784 [VanA]). The MICs of ceftobiprole for 50 and 90% of the isolates tested were 0.25 and 1 μg/ml, respectively. All Bla producers and vancomycin-resistant isolates were inhibited by concentrations of ≤1 and ≤4 μg/ml, respectively, at the standard inoculum concentration. Ceftobiprole MICs at a high inoculum concentration for a subset of five Bla+E. faecalis isolates were ≤1 μg/ml. Bactericidal activity was observed against four isolates tested at concentrations as low as 1 μg/ml regardless of the production of β-lactamase or vancomycin resistance. A combination of ceftobiprole (0.5 μg/ml) and streptomycin (25 μg/ml) was synergistic against Bla+ TX0630 and TX5070. Ceftobiprole (0.5 μg/ml) plus gentamicin (10 μg/ml) was synergistic against VanB isolate TX2484 and showed enhanced killing, but not synergism, against TX2784 (VanA), despite the absence of high-level resistance to gentamicin. In conclusion, ceftobiprole exhibited good in vitro activity against E. faecalis, including Bla+ and vancomycin-resistant strains, and exhibited synergism with aminoglycosides against selected isolates.